Chemical and Morphological Control of Interfacial Self‐Doping for Efficient Organic Electronics. Issue 15 (5th March 2018) - Liu, Yao; Cole, Marcus D.; Jiang, Yufeng; Kim, Paul Y.; Nordlund, Dennis; Emrick, Todd; Russell, Thomas P.
Abstract: Solution‐based processing of materials for electrical doping of organic semiconductor interfaces is attractive for boosting the efficiency of organic electronic devices with multilayer structures. To simplify this process, self‐doping perylene diimide (PDI)‐based ionene polymers are synthesized, in which the semiconductor PDI components are embedded together with electrolyte dopants in the polymer backbone. Functionality contained within the PDI monomers suppresses their aggregation, affording self‐doping interlayers with controllable thickness when processed from solution into organic photovoltaic devices (OPVs). Optimal results for interfacial self‐doping lead to increased power conversion efficiencies (PCEs) of the fullerene‐based OPVs, from 2.62% to 10.64%, and of the nonfullerene‐based OPVs, from 3.34% to 10.59%. These PDI–ionene interlayers enable chemical and morphological control of interfacial doping and conductivity, demonstrating that the conductive channels are crucial for charge transport in doped organic semiconductor films. Using these novel interlayers with efficient doping and high conductivity, both fullerene‐ and nonfullerene‐based OPVs are achieved with PCEs exceeding 9% over interlayer thicknesses ranging from ≈3 to 40 nm. Abstract : Self‐doping of perylene‐diimide‐based ionenes enables chemical and morphological control of interfacial doping and conductivity in organic electronic devices. Using these materials provides a straightforward and controllable method to modulate the interface between electrodes and active layers, affording both fullerene‐ and nonfullerene‐based solar cells with high efficiencies over a wide range of doped interlayer thicknesses.